Microbiological criteria proposal for camu-camu pulp (Myrciaria dubia H.B.K. McVaugh) semi-processed and frozen - Ramos, Félix G. (2019)
In Peru, one of the main difficulties in the processing of frozen camu-camu pulp is to obtain fresh fruit with good quality, because it is damaged during the transportation from the Amazon to Lima, place where are located the processing factories. To avoid that fruit lots arrive with high percentages of damaged fruit, it is preferred to buy camu-camu pulp semi-processed and frozen, thus reducing risks during transport. This raw material is washed, pulped and frozen in the place of harvest or collection area, and then sold to processing factories in Lima, where it is refined, standardized, heat treated and frozen to obtain a product of long life, which is marketed and exported. The characteristics of this fruit make it a low risk to health, not allowing the growth of pathogenic bacteria, due to its physicochemical characteristics and the presence of phytochemicals, for this reason the microorganisms of interest for these raw materials are the spoilages. The present work was developed at a processing factory of fruit pulp in Lima, to establish microbiological criteria (MC) for this raw material, based on the results of evaluations of total counts of bacteria, molds, yeasts and total coliforms, during the reception. The MC proposed allows to accept 1 good lot with an 80% of probability and accept 1 bad lot containing 50% of defectives with 13% of probability.